Sighting the New Moon as the Methodology for Determining the Month of Ramadhan - Morad Sabdullah Umpa (Philippine Association of Institutions for Research, Inc., 2018)
Muslim communities are known to be united, but every year, towards the start of Ramadhan, some of them argue which started to be divided over the issue on the determination of the start of the blessed month. This study aimed to investigate the different options proposed for the determination of the month of Ramadhan including local and global sighting; Number of witnesses required; Size of Matla'; and Saudi Sighting Process and its implications. Data were gathered through an in-depth study using the descriptive method. The objectives were to determine the universally accepted legal opinion on sighting the New Moon in connection with the elimination of differences that frequently surface and for ensuring the celebration of 'Eid on a single day in one lunar unit. Based on the findings, it is revealed that sighting the new moon must be conducted in each locality because there are Multiple Horizons (the time at which the moon rises, varies from place to place). Muslims must show unity during the month of Ramadhan and at the occasions of 'Eid at least locally if not nationally or internationally. This would be of great value and importance to the whole Muslim nation by fostering the initial steps towards united observance of Ramadhan.